Evaluation of relationship between Enterobius vermicularis infection and bruxism in children - Özge Şentürk; Kadriye Görkem Ulu Güzel; Yavuz Tokgöz (Arbu Academic Publishing, 2022)
Aim: To investigate the relationship between Enterobius vermicularis infection and bruxism in children. Methods: Twenty-six children (aged 3-10 years), who were systemically healthy, showed teeth-grinding at least once a week in the last 3 months, and applied to Aydın Adnan Menderes University Faculty of Medicine Hospital Child Gastroenterology Clinic were recruited and allocated into two groups: positive for E. vermicularis infection (Group 1, n = 13); negative for E. vermicularis infection (Group 2, n = 13). The children were examined clinically, and a survey was administered, to be filled in by the children's parents. BiteStrip was used to determine the level of bruxism. Results: Sixteen males (mean age: 7.3±1.6 years) and 10 females (mean age: 7.3±2.4) were included in the study. There was no significant difference between genders. Severe bruxism occurred in 46.2% and 30.8% of Groups 1 and 2, respectively. No significant correlation existed between E. vermicularis infection and BiteStrip scores. Conclusions: Enterobius vermicularis infection did not affect the occurrence of bruxism in the paediatric population evaluated.